Sravnitel'nyj analiz osnovnych pokazatelej I i II evropejskich igr - Leontyeva, L. S.; Leontyeva, N. S.; Koreneva, M. V.; Belinsky, D. V.; Alexandrov, S. G. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article is devoted to the new phenomenon in the international Olympic sports - the European Games, which were held for the first time in the Azerbaijani city of Baku in 2015, four years later, the II European Games took place in Minsk (Republic of Belarus). The study provides a comparative analysis of the main indicators and results of the I and the II Games, including, number of countries, number of participants, competition leaders, number of medals, etc. The research methods: collection, analysis and systematization of statistical materials, inductive and deductive methods. The results, obtained during the study, will be included in the historical and sports disciplines.